Students’, Teachers’ and Farmers’ Mastery of Knowledge on the Use and Benefits of Herbicides in Four Communities in Birim South District, Ghana - Boatey, G. O.; Hordzi, W. H. K. (Journal of Biology and Life Science, 2024)
Rampant farmer application of herbicides involving students in agriculture in Ghana, especially in Birim South District is a major concern for stakeholders. This problem can be reversed if stakeholder knowledge about appropriate ways of application and usefulness of herbicides is known. Hence, this study determined views of Junior High School students, their teachers and farmers in Birim South District of Ghana about the usefulness and appropriate application of herbicides. Ninety students, 30 teachers and 60 farmers randomly and conveniently selected participated in a cross-sectional survey in the District. Expert validated questionnaire with Cronbach alpha reliability coefficient of .0.75 was used. There were eight close-ended items. Questionnaires were personally administered and analysed descriptively. Students (mean =2.3), teachers (mean = 2.7) and farmers (mean = 3.6) were all familiar with herbicides but farmers were most familiar. All teachers and farmers and 93.33% of students agreed that herbicides are primarily used to control weeds. Opinions about cost-effectiveness of herbicides were highly varied. There were also varied opinions about practices farmers could adopt to minimize risks associated with herbicide application. All respondents had some misconceptions about usefulness and appropriate ways of herbicide application. The implication is that there should be education programmes to help stakeholders to consolidate the right information and empower them with more knowledge to do away with the misconceptions.